Understanding the Patient Experience with Twice-Nightly Sodium Oxybate Therapy for Narcolepsy: A Social Listening Experiment - Maria Picone; Frederik Ascencion; Matthew Horsnell; Enming Zhang; Lauren Dougherty; Christopher DeFelice; Maurice Flurie; Rachelle Cook; Anne Marie Morse; Luis E. Ortiz; E. Robert Wassman; Jennifer Gudeman (Brain Sciences)
Background/Objectives: Narcolepsy is a chronic neurologic disorder associated with substantial challenges that affect the social, emotional, and financial quality-of-life domains. A social listening analysis and structured survey were conducted to better understand the candid perspective of people with narcolepsy (PWN) and their experience with twice-nightly sodium oxybate (SXB). Methods: To characterize conversations and experiences in narcolepsy communities where SXB was mentioned, a social media analysis was conducted from August 2011 to October 2022. A structured survey was administered to PWN taking oxybate therapy from October 2022 to November 2022. Results: From the social media analysis, the largest topic was related to “cataplexy”, with 537 posts/comments. The most frequent term was “xyrem”, with 22,200 mentions. Of the 87 survey respondents, 85 respondents had narcolepsy, 75.3% (64/85) reported missing their second dose of immediate-release SXB or mixed-salt oxybates, and 58.8% (50/85) of respondents reported that they took their second dose of oxybate > 4 h after the first dose. Respondents reported poor sleep quality as the greatest effect or issue experienced after missing their second oxybate dose. When respondents were asked whether they had ever been injured after waking to take their second oxybate dose, 31.8% (27/85) of respondents reported an injury. Conclusions: PWN taking twice-nightly oxybates often report inconsistent adherence to the prescribed dosing, which results in negative consequences in their lives. This research provided an anonymized forum for PWN to voice challenges with middle-of-the-night awakenings that they may be reluctant to explain to their clinician.